Moral Psychopharmacology Needs Moral Inquiry: The Case of Psychedelics - Langlitz, Nicolas; Dyck, Erika; Scheidegger, Milan; Repantis, Dimitris (Frontiers in Psychiatry, 2021)
The revival of psychedelic research coincided and more recently conjoined with psychopharmacological research on how drugs affect moral behavior. This article makes the case for a moral psychopharmacology of psychedelics that examines whether psychedelics serve as non-specific amplifiers that enable subjects to reconnect with their values, or whether they promote specific moral-political orientations such as liberal and anti-authoritarian views, as recent psychopharmacological studies suggest. This question gains urgency from the fact that the return of psychedelics from counterculture and underground laboratories to mainstream science and society has been accompanied by a diversification of their users and uses. We propose to bring the pharmacological and neuroscientific literature into a conversation with historical and anthropological scholarship documenting the full spectrum of moral and political views associated with the uses of psychedelics. This research program sheds new light on the cultural plasticity of drug action and has implications for the design of psychedelic pharmacopsychotherapies. It also raises the question of whether other classes of psychoactive drugs have an equally rich moral and political life.